Slope stability analysis at Pit AI-Block B PT. Anugerah Alam Andalas Muara Ketalo Village, Sungai Bengkal, Tebo Ilir Subdistrict, Tebo District, Jambi Province - Dasri Husien; Bambang Heriyadi; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2018)
Slope stability was not currently analysed into mining production at company. Bishop Simplified and Janbu Simplified will be applied to the slopes.Data bases are Top Soil: Unit Wight (γ)= 20,36 kN/m3, Cohesion (c') =26,38 kN/m2 and angle of repose (ϕ') = 25,5°.Sands: Unit Wight (γ) = 22,19 kN/m3, Cohesion (c') = 28,14 kN/m2 and angle of repose (ϕ') = 33,3°. Clay: Unit Wight (γ) =19,67 kN/m3, Cohesion (c') = 32,16 kN/m2 and angle of repose (ϕ') = 39,11°. Initial Slope height 22 metre and overall slope angles are 46°, Single Slope height I 5 metreand slope angle 48°, Single Slope Height II 17 metre and slope angle 55°.Geometrical slope recommendations are: 1. Bishop Simplified Method SF 0,892, slope is not safe. Reducing slope angle (46° to 30°) increasing II single slope to III single slope and height 6,115, 8,885, 7 metre, angels 30°,39°, 56°, berm I 4,221 metre berm II 4,601 metre, SF is now 1,338, slope is safe. 2. Janbu Simplified Method (saturated) SF 0,784, slope is not safe. Reducing slope angle (46° to 30°) and increasing II single slope to III single slope and height 6,115, 8,885, 7 metre, then angle 28°,32°, 56°, berm I 2,689 metre and berm II 4,601 meter, SF is1,337 and slope is safe.